The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1111/j.1365-2923.1986.tb01058.x
|View full text |Cite
|
Sign up to set email alerts
|

Do medical students learn from multiple choice examinations?

Abstract: Fifty-two students sat two 60-question multiple choice examinations 8 months apart. The second examination consisted of 30 of the questions used at the first sitting, together with 30 questions with repeated stems but different responses. Immediately after the first sitting, 27 of the students went through the paper with the examiner. They were given the correct answers, and any problems were discussed. For the 30 questions with new options, the increase in marks was similar in the two groups. The group given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…Similar increases in truth ratings have been found after reading false items on true-false tests (Toppino & Brochin, 1989). Likewise, a re-test with novel lures yields better performance than a re-test with old lures (Rees, 1986), because initial testing increases the perceived truth-value or familiarity of the lures (Jacoby, Shimizu, Daniels, & Rhodes, 2005). In a more direct demonstration, Roediger and Marsh (2005) showed that taking a multiple-choice test increased production of lures as answers on a final general knowledge test, even though subjects were warned against guessing.…”
supporting
confidence: 67%
“…Similar increases in truth ratings have been found after reading false items on true-false tests (Toppino & Brochin, 1989). Likewise, a re-test with novel lures yields better performance than a re-test with old lures (Rees, 1986), because initial testing increases the perceived truth-value or familiarity of the lures (Jacoby, Shimizu, Daniels, & Rhodes, 2005). In a more direct demonstration, Roediger and Marsh (2005) showed that taking a multiple-choice test increased production of lures as answers on a final general knowledge test, even though subjects were warned against guessing.…”
supporting
confidence: 67%
“…This phenomenon represents the memorial effects of exposure to misinformation and has been described (see Brown et aL, 1999) as the Negative Suggestion Effect (NSE). The robustness of the NSE has been demonstrated during multiple-choice tests (e.g., Rees, 1986), true-andfalse tests (e.g. , Toppino & Brochin , 1989), and spelling tests (e.g., Brown, 1986;Jacoby & Hollingshead, 1990).…”
Section: Repetition Of Inaccurate Perseverative Responding Responsesmentioning
confidence: 99%
“…6 ' 7 MCQs may be useful in self-directed learning, 8 and there is evidence of useful student learning from feedback to students who have taken MCQ examinations. 9 The interactive nature of our postexamination review process facilitates discussion and debate and is an active, student-centered teaching activity that might be expected to enhance learning. The students in our study were enthusiastic about the learning experience, and our faculty reviewers were impressed that it was a useful learning experience for both the students and themselves.…”
Section: Discussionmentioning
confidence: 99%